(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Peribulbar lignocaine anaesthesia is commonly used in ophthalmic surgeries. Aim. To identify the effect of ocular digital compression (ODC) following peribulbar anaesthesia (PBA) on the optic nerve. Setting. A hospital-based prospective non-controlled observational study done at Sankar Foundation Eye Institute, Visakhapatnam, India. Method. This study conducted on 124 patients aged ≥40 years with non-complicated cataract. All patients were randomly divided into two groups by computer generated database; group 1 for PBA with ocular digital compression and group 2 for PBA without compression. The patient’s eye was dilated, administered 2% lignocaine hydrochloride 5 mL, 0.75% bupivacaine 5 mL, and hyaluronidase 75 IU/mL injection for the peribulbar block(PBA). Vision and relative afferent pupil defect (RAPD) reactions were noted at 1 min and 10 mins after anaesthesia in both groups. Results. Out of 61 (PBA+ODC) cases, vision drop was seen in 33 (54.09%) after 1 min, and 28 (45.91%) patients has no change in the vision after 1 min, and 10 min, and 29 (47.54%) cases had RAPD after 1min, 32 (52.45%) cases had RAPD after 10 min, 32 (52.45%) cases had NSRL after 1min, 29 (47.5%) cases had NSRL after 10 min. This implies during 10 min compression, there is an appearance of RAPD in the previously NSRL eye. Out of 63 patients of PBA without ODC group, vision drop is seen in 48 (76.19%) after 1 min and 10 min. In this group, 57(90.4%) cases had RAPD after 1 min. and 56 (88.8%) cases had RAPD after 10min. 6 (9.5%) cases had NSRL after1 min. 7 (11.1%) cases had NSRL after 10 min. Males had more vision drop in the compression group. 33 (54.09%) cases in group 1 and 48 (76.19%) cases in group 2 had vision drop at 1min and 10 min. In compression group, 29 (47.5%) cases had RAPD 1 min, and 32 (52.45%) cases had RAPD at 10 min. In the non-compression group, 57 (90.47%) cases had RAPD at 1min, and 56 (88.88%) had RAPD at 10 min. The age of >60 yrs patients had more vision drop and RAPD irrespective of compression than the 40-60 yrs of age group, which shows that vascular changes may contribute to decreased optic nerve perfusion. Conclusion. The non-compression group had more vision drop and RAPD than the compression group. Age of >60 yrs and males had more percentage of vision drop.